Peran Sektor Pertanian dalam Mengurangi Ketimpangan Pendapatan di Wilayah Papua Sebelum dan Sesudah Otonomi Khusus - Siti Halimatus Sa'diyah; Irham Irham (Agro Ekonomi, 2016)
This study aims to determine: (i) the contribution of agriculture sector to GDP growth in the region before and after the Papua special autonomy, (ii) the level of income inequality per capita in the region before and after the Papua special autonomy, (iii) the role of agriculture in reducing income inequality in the community before and after the region Papua special autonomy, and (iv) the effect of investment, labor force, the allocation of funds for regional development, agglomeration in the region Papua, and policy implementation of special autonomy to Papua region against income inequality.Data used in this research is secondary data from the years 1993-2013 and analyzed using analysis of contribution, growth, income inequality (Williamson index, and multiple linear regression with OLS method. The analysis showed that the agricultural sectors contribution to GDP growth before special autonomy greater than after the special autonomy. Furthermore, per capita income inequality between regions in Papua special autonomy after the bigger (more unequal). The agricultural sector play a greater role in reducing income inequality communities in Papua after special autonomy than before the special autonomy. Investment in Papua per capita, regional development aid funds allocated per capita, and agglomeration in Papua positive effect on income inequality between regions in Papua. Index of income inequality between regions in Papua after special autonomy (the period 2002-2013) is greater than before the special autonomy (the period 1993-2001)